Initial Development and Psychometric Evidence of Physical Education Grit Scale (PE-Grit) - Noomen Guelmami; Noomen Guelmami; Noomen Guelmami; Nasr Chalghaf; Nasr Chalghaf; Nasr Chalghaf; Amayra Tannoubi; Amayra Tannoubi; Amayra Tannoubi; Amayra Tannoubi; Luca Puce; Fairouz Azaiez; et al. (Frontiers Media S.A., 2022)
BackgroundGrit is a key concept in positive psychology and educational science. The construct measures two related constructs that are interest and effort. Several instruments have been developed to measure this construct in professional and educational contexts, but no tools have been developed considering specific contexts such as physical education and sport.ObjectivesThe objective of this study is to develop and test a measurement scale to assess Grit in the context of physical education and sport.MethodsTwo exploratory (Phase 1) and confirmatory (Phase 2) samples were administered the 16-item PE-Grit scale in Arabic. In addition, the confirmatory sample also was administered the R-SPQ-2F two-factor learning approaches scale. The factor structure was examined first by exploratory factor analysis on the first sample and then by confirmatory factor analysis on the second sample. Reliability testing was performed by checking internal consistency simultaneously by the three indices: McDonald's ω, Cronbach's α and Gutmann's λ6. Concurrent validity was checked by Pearson's correlation between the PE-Grit and the two dimensions of the SPQ-2F.ResultsAfter the exploratory factor analysis, which identified the factors and gave a preliminary validation of the designed instrument, confirmatory factor analysis was performed on three hierarchical models to be able to identify the best fitting model. A third-order hierarchical model with two physical and academic components each formed by interest and effort presented the best fit indices: chi X2 = 192.95 (p < 0.01), and the X2/DF = 1.36; GFI = 0.99; AGFI = 0.99; CFI and TLI close to 1; RMSEA = 0.025. In addition, McDonald's ω, internal consistency, and Gutmann's λ6 ranged from 0.78 to 0.86 for all four scale dimensions.ConclusionThe PE-Grit scale displays adequate factor structure, good reliability, and acceptable concurrent validity and can be administered to assess Grit in physical education and sport students.